Peran Subsektor Peternakan dalam Perekonomian Jawa Barat - Wiradimadja, Ichwansyah; Mahardika, Muhammad Naufal; Putra, Orlanda Mahari; Firman, Achmad (Universitas Galuh, 2025)
The livestock subsector contributes significantly to meeting the need for animal protein and improving the local economy. The study aims to analyze the development of beef, poultry, egg, and milk production, as well as the economic growth of the livestock subsector in West Java. In addition, the study also highlights the number of workers involved and investment in the livestock subsector. This study uses secondary data from the West Java Central Statistics Agency and related agencies. The results of the study show fluctuations in meat and egg production from 2020 to 2023, with poultry and egg production of laying hens experiencing a significant increase. However, the number of workers in this subsector has tended to decline in recent years, in line with the decline in the number of livestock business households. On the other hand, investment in the domestic (PMDN) and foreign (PMA) livestock subsectors has increased significantly, especially in cattle and poultry farming. These results indicate that the livestock subsector in West Java has a strategic role in supporting the local economy, despite the challenges of production fluctuations and a decline in the workforce.